2013
DOI: 10.1016/j.juro.2013.01.102
|View full text |Cite
|
Sign up to set email alerts
|

Protein Markers of Malignant Potential in Penile and Vulvar Lichen Sclerosus

Abstract: Only a minority of lichen sclerosus cases are associated with squamous cell carcinoma. However, the therapeutic implications of a squamous cell carcinoma diagnosis are severe. Clinically, we lack an understanding of how to separate indolent lichen sclerosus cases from those in danger of progression to squamous cell carcinoma. Several protein markers show promise for further delineating the pathobiology of lichen sclerosus and the potential malignant transformation into squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…Non‐neoplastic epithelial disorders of the vulva are a group of chronic diseases occurring in females, manifesting as degeneration of the vulval skin and mucosa and pigment changes, and characterised by severe itch and burning pain in vulva, depigmentation or whitening of lesion skin and mucosa, and changes in the skin such as rough, chapped and broken skin. Up until now, patients with atrophy of the vulva, vaginal introitus stenosis and dyspareunia have had a poor sexual life and life quality . The underlying mechanism for the pathogenesis of NNEDV has been thought to be related to immunity, infection, hormone or genetic factors, but the cause remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐neoplastic epithelial disorders of the vulva are a group of chronic diseases occurring in females, manifesting as degeneration of the vulval skin and mucosa and pigment changes, and characterised by severe itch and burning pain in vulva, depigmentation or whitening of lesion skin and mucosa, and changes in the skin such as rough, chapped and broken skin. Up until now, patients with atrophy of the vulva, vaginal introitus stenosis and dyspareunia have had a poor sexual life and life quality . The underlying mechanism for the pathogenesis of NNEDV has been thought to be related to immunity, infection, hormone or genetic factors, but the cause remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…VLS not only affects quality of life, but is also associated with an increased risk of squamous cell carcinoma (SCC) of the vulva. The increased risk of developing squamous cell carcinoma is approximately 5% in patients with lichen sclerosus . However, the aetiology of NNEDV remains unknown, and such diseases are considered common but refractory.…”
Section: Introductionmentioning
confidence: 99%
“…55 The authors also suggested the involvement of gH2AX in different biological mechanisms as an early event leading to resistance to apoptosis in vulvar carcinogenesis. 56 Carlson et al 57 indicate that gH2AX is overexpressed in lichen sclerosus of the vulva/ penis and squamous cell carcinoma. Brunner et al 58 investigated the role of gH2AX in endometrial tumorigenesis.…”
Section: Gh2ax Studies: Biosamplingmentioning
confidence: 99%
“…Recently, several markers—including p53, Ki67 and γH2AX among others—have been used to this effect in HPV related tumorigenesis [3]. …”
Section: Introductionmentioning
confidence: 99%